Pengaruh Gaya Kepemimpinan Dan Budaya Kerja Terhadap Kinerja Karyawan PT. Nijes Bayu Lestari - Budi Purnomo (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The formulation of the problem in this study is how much influence leadership style and Work Culture have on the performance of PT employees. Nijes Bayu Lestari. The purpose of this study is to find out how much influence work culture and work career have on the performance of PT employees. Nijes Bayu Lestari. Based on the results of the study, it was found that for the effect of variables X1 (Style of Leadership) and X2 (Work Culture) on Y (Employee Performance) need to be analyzed by the author because Employee Performance is work achieved by a person or group of work or activities that have been done. Performance can only be obtained if a person or group is doing work or activities. Therefore, without doing something, neither individuals nor groups will be possible. By identifying Work Motivation and Employee Ability, it will have an impact on employee performance. Based on the above thoughts according to the researcher hypothesis which states that Leadership Style and Work Culture have a strong influence on Employee Performance di PT Nijes Bayu Lestari. The magnitude of the influence of both independent variables with dependent variables also shows the reality of how to implement and improve optimal Employee Performance, this fact has been answered with Leadership Style and Good Work Culture. Practically, the two variables run together, meaning that in the process of Leadership Style and Work Culture can be variables or factors that determine whether employee performance is good or bad. If the Leadership Style is good / and Buya Work is good, then by itself Employee Performance will increase.